Pollination ecology of Clerodendrum indicum (Lamiaceae): first report of deceit pollination by anther-mimicking stigma in a bisexual flower - Ghosh, Arijit; Pal, Pankaj K. (Revista de Biología Tropical, 2017)
Clerodendrum indicum (Lamiaceae) is a medicinally important shrub. We have studied the details of its pollination ecology which was hitherto unknown. The work was done during three consecutive years 2012-2014, based on 118 plants occurring in three widely separated wild populations in West Bengal, India, together with 25 individuals grown in an experimental plot. Details of flower structure and dynamics of floral events, pollen production and pollen dispersal, visitors and pollinators, floral attractants and floral rewards and pollen transfer mechanism have been worked out by standard methodologies with a 10x high resolution hand lens (IRL), a Leica WILD M3B Stereo-binocular microscope (Switzerland) and a Leica DMLB compound bright field light microscope (Germany). The tubular flower of four-day longevity attracts its visitors by visual cues. Flowers are visited regularly by ten species of insects. On the basis of the visitor behaviour, these can be classified into three distinct categories, viz., visitors belonging to Category-I act on cushion and trichome nectaries of calyx and corolla respectively, those of Category-II act on the dehisced anthers and trichome nectaries of corolla while those of Category-III act on dehisced anthers as well as receptive stigma. Majority of the visitors belong to either Category-I or Category-II. They visit only the 2nd day flowers and never visit a 3rd day flower when the stigma assumes receptivity. Therefore, they are not regarded as pollinators but, act as pollen and/or nectar robbers. Those are discriminated by offering secretions from extra-nuptial nectaries of the flower. Visitor species of Category-III, represented by a species of Trigona, constitute the legitimate pollinator of the plant and thereby, making the plant monophilic. Pollen presentation from the bisexual, dichogamous and protandrous flower takes place on the 2nd day, while the stigma assumes its receptivity on the 3rd day of flower opening. Pollen transfer to the body of the pollinator by a 2nd day flower in its male phase is achieved by offering edible pollen grains. On the other hand, a 3rd day flower at its female phase is devoid of the reward (pollen grain). The yellow shiny receptive stigma of such a flower strikingly mimics the freshly dehisced anthers and the pollinators being lured by such a stigma inadvertently transfer pollen onto it. C. indicum is so far the only known species of flowering plants where deceit pollination occurs by anther-mimicking stigma in a bisexual flower.